Self-concept and engagement of trainees attending the training courses for petty officers 1st class - Frade, Ana (2017)
Conceptual Framework: Self-perceptions influence individuals’ receptiveness to the task and the way they pursue its accomplishment. Therefore, it is of the uttermost importance to analyze the influence of trainee self-concept in their engagement toward tasks. Objectives: The present study aims to analyze how self-concept influences the engagement of trainees attending the Training Courses for Petty Officers 1st Class (CFS). Methodology: The study methodology made use of the Utrecht Work Engagement Scale (Schaufeli, Salanova, González-Romá & Bakker, 2002), the Assessment Scale for Trainee Engagement in the Portuguese Navy (Frade & Veiga, 2014; Frade, 2015), as well as the Assessment Scale for Trainee Self-concept in the Portuguese Navy (Frade & Veiga, in press; Frade, 2015). The sample was comprised of 149 trainees from the CFS of the Portuguese Navy. The data collected were analyzed using SPSS software. Results: The results point to the important influence of selfconcept in the engagement dimensions as a way to encourage the engagement of trainees from the Portuguese Navy. Suggestions to future studies are presented.